Analisis Kebutuhan Pelatihan Guru IPA Berbasis Kompetensi Kepribadian - Irma Febrianis; Pudji Muljono; Djoko Susanto (Jurnal Penyuluhan, 2014)
Deviant behavior and ethic, norm, and moral violations done by the teachers become indicators on how poor is the personalcompetence of the teachers in Indonesia. Training to improve the personal competence of the teachers has got less concern fromthe government. This study offers an alternative in determining the training needs using the Training Needs Assessment (TNA).The study aimed at mapping the actual personality competence of the teachers, establishing training needs and priorities, aswell as providing recommendations for effective training methods. The survey method, interviews and FGDs were conductedto obtain the primary data. Survey was carried on 165 natural science teachers of SMP Negeri Pekanbaru using self evaluationquestionnaire. Result show that actual personality competence of the teachers are below the ideal competence. There are twopriority training programs include the training i.e on ethic code of teachers and training on personality strengthening. The trainingmethods of internal coaching and specific training are effective to improve the personality competence of the teacher.Keywords: personality competence, training needs analysis, teacher